Pengembangan Sistem Informasi Pendaftaran Santri Berbasis Web Menggunakan Agile Scrum dan Evaluasi System Usability Scale (SUS) - Mohamad Roikhan Makhmud; Endang Wahyuningsih (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
The registration process for new students in many Islamic boarding schools is still done manually, causing efficiency constraints, service delays, and data management errors. This condition indicates that digital transformation in traditional Salaf Islamic boarding schools still faces challenges, especially related to user acceptance with varying levels of digital literacy. This study aims to develop a web-based student registration information system at Darussalam Adikarso Islamic Boarding School in Kebumen using the Agile Scrum approach and evaluate the system's usability using the System Usability Scale (SUS). The study used the Research and Development (R&D) method with Scrum stages including product backlog, sprint planning, sprint development, sprint review, and sprint retrospective. System testing was conducted using Black Box Testing, while the usability evaluation involved 21 respondents consisting of prospective students, guardians, and Islamic boarding school administrators. The results showed that all main features of the system run according to functional requirements. The usability test resulted in an average SUS score of 81.19 which is included in the Acceptable category with a grade A and an adjective rating of Excellent. The research findings show that the Agile Scrum approach is able to support the development of a system that is adaptive, easy to use, and in accordance with user needs in a traditional Salaf Islamic boarding school environment, thus potentially increasing the effectiveness and efficiency of student registration administration.